2017
DOI: 10.1186/s12889-017-4817-3
|View full text |Cite
|
Sign up to set email alerts
|

A push for public health: the effect of e-bikes on physical activity levels

Abstract: BackgroundCycling is considered to have a positive effect on public health through increased physical activity. In Norway, the e-bike is seen as a way of getting more people to cycle. However, the motorized assistance of an e-bike potentially eliminates any physical activity associated with its use. It is possible that the assumed health effect of increased cycling is “erased” through a reduction in other physical activities (a substitution effect). In this paper we study the public health effects of e-bikes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…However, e-bikes appear to be used more frequently as a utilitarian mode of transport rather than for a leisure activity. Studies with samples aged ≤55years reported the e-bike being used primarily for commuting ( Dill and Rose, 2012 ; Winslott Hiselius and Svensson, 2017 ; MacArthur et al, 2014 ; Plazier et al, 2017a ; Popovich et al, 2014 ; Schleinitz et al, 2014 ; Cappelle et al, 2003 ; Kairos, 2010 ; MacArthur et al, 2018 ; Lobben et al, 2019 ; Behrendt, 2018 ; Sundfør and Fyhri, 2017 ) whilst older adults used the e-bike for shopping and visiting friends but rarely for commuting. In addition, older adults used the e-bike for recreational purposes.…”
Section: Resultsmentioning
confidence: 99%
“…However, e-bikes appear to be used more frequently as a utilitarian mode of transport rather than for a leisure activity. Studies with samples aged ≤55years reported the e-bike being used primarily for commuting ( Dill and Rose, 2012 ; Winslott Hiselius and Svensson, 2017 ; MacArthur et al, 2014 ; Plazier et al, 2017a ; Popovich et al, 2014 ; Schleinitz et al, 2014 ; Cappelle et al, 2003 ; Kairos, 2010 ; MacArthur et al, 2018 ; Lobben et al, 2019 ; Behrendt, 2018 ; Sundfør and Fyhri, 2017 ) whilst older adults used the e-bike for shopping and visiting friends but rarely for commuting. In addition, older adults used the e-bike for recreational purposes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, survey data on early adopters in Australia, reported e-bike owners to have lower education and income, yet higher age, than the population in general (Wolf and Seebauer, 2014). Other studies recruiting convenience samples from e-bike retailers (Hiselius and Svenssona, 2014; Sundfør and Fyhri, 2017), found the appeal to e-bikes to be stronger among those with little interest in, and low levels of PA in general, and also differing motivation for buying an e-bike between the younger and the elderly.…”
Section: Introductionmentioning
confidence: 98%
“…Inadequate physical activity is associated with an increased risk of obesity with consequences including development of many chronic diseases leading to significant morbidity, premature mortality and economic loss [1][2][3][4][5]. The Centers for Disease Control and Prevention (CDC) recommend that adults meet the goal of 150 minutes of moderate-intensity aerobic activity or 75 minutes of vigorous aerobic activity per week [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, when measured by accelerometers, these self-reported statistics were grossly over-estimated, with less than 5% of U.S. adults meeting the CDC recommendations in 2008 and 29% of New Yorkers meeting the recommendations in 2011 [9][10][11]. While vigorous physical activity achieves the highest level of fitness, the greatest health effects are seen in those individuals who progress from being sedentary to completing moderate physical activity regularly [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation